Clusia goscinnyi, a new species of Clusia section Oedematopus (Clusiaceae) - Nascimento-Jr, José E. Do; Bittrich, Volker; Amaral, Maria Do Carmo E. (Phytotaxa, 2017)
A new species of Clusia sect. Oedematopus is described and illustrated. The species can be distinguished from others in this section mainly by its 14–31 stamens in staminate flowers, 8–10 staminodes in pistillate flowers and discontinuous secretory canals visible on the abaxial surface of the leaf blade.